2009
DOI: 10.1007/s12598-009-0030-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ce3+ doping on the structure and magnetic properties of Mn-Zn ferrite fibers

Abstract: Ce 3+ -doped Mn-Zn ferrite fibers were successfully prepared by the organic gel-thermal decomposition method from metal salts and citric acid. The composition, structure, and magnetic properties of these ferrite fibers were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), and vibrating sample magnetometer (VSM). The results show that Mn 0.2 Zn 0.8 Fe 2−x Ce x O 4 (x = 0-0.04) fibers are featured with an average grain size of 11.6-12.7 nm, with diameters ranging between 1.0 to 3.5 μ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…The Ce ion is known to offer substantial hybridization of the 4f states with 3d bands due to the existence of a larger 4f band. The improvement of electromagnetic characteristics of Li ferrite after Ce doping [34] and the enhancement of saturation magnetization with a decrease in coercivity in Ce doping Mn-Zn ferrite [35] are both interesting topics. Many methodologies are used for the synthesis of nanoparticles, either by an electrochemical method, an electrodeposition method [36], or a cathodic electrodeposition method (CED), etc.…”
Section: Introductionmentioning
confidence: 99%
“…The Ce ion is known to offer substantial hybridization of the 4f states with 3d bands due to the existence of a larger 4f band. The improvement of electromagnetic characteristics of Li ferrite after Ce doping [34] and the enhancement of saturation magnetization with a decrease in coercivity in Ce doping Mn-Zn ferrite [35] are both interesting topics. Many methodologies are used for the synthesis of nanoparticles, either by an electrochemical method, an electrodeposition method [36], or a cathodic electrodeposition method (CED), etc.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Fig. 3a no changes occurred in the position of the reections due to the inclusion of Ce 3+ for Fe 3+ , only a variation in the lattice constant 21 values were observed because of a great deviation in the ionic radius of metal ions (Ce 3+ ¼ 1.3 Å; Fe 3+ ¼ 0.64 Å). The variation of lattice constant values derived from XRD data are given in Fig.…”
Section: Resultsmentioning
confidence: 89%
“…Also, the eddy current losses related to electrical resistivity were also reduced. Xiang et al [173] prepared MnZn ferrite particles with Ce 3+ doping and observed that no impurity phase was detected in the XRD pattern. It confirmed that Ce ions entirely got dissolved in spinel structure.…”
Section: Synthesis Methods To Prepare Mnzn Ferritesmentioning
confidence: 99%